Model of Green Competitive Advantage Through Green Leadership, Green Intellectual Capital, and Environmental Ethics in Industrial Enterprises in Indonesia - Sudarno; Panjaitan, Harry; Rahman, Sarli; Hutahuruk, Marice; Mujiono (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This study aims to analyse and empirically substantiate the theory of the relationship between green leadership, green intellectual capital, and environmental ethics on green competitive advantage in food and beverage companies in Indonesia. This study's population is companies in Indonesia's food and beverage industry. The sampling technique is conducted by summing the highest indicators of each variable multiplied by 5-10. The number of samples was calculated as many as 110 samples. The primary source of this research data is in the form of questionnaires, and secondary data is in the form of articles, books, and other supporting documents. Data collection techniques are used in Questionnaire instruments. Data analysis techniques include descriptive analysis and multiple linear regression analysis with the help of Smart PLS 4.0 software. The results of this study prove that green leadership, green intellectual capital, and environmental ethics have a positive and significant effect on green competitive advantage. The results of this study provide real implications for green leadership, green intellectual capital, and ecological ethics in determining environmentally friendly environmental policies to achieve a competitive advantage for food and beverage industry companies in Indonesia.